Steady-state response of flexible combined pile-raft foundation under dynamic loading. Issue 145 (June 2021) - Bhaduri, Aniruddha; Choudhury, Deepankar
Abstract: The present study proposes a closed-form solution of flexible combined pile-raft foundation (CPRF) resting on an elastic medium under dynamic loading. Two components of the foundation system, i.e. pile and raft are idealized as beam and plate, respectively, resting on an elastic two-parameter Pasternak soil medium. The governing differential equations of these components under horizontal harmonic loading is formulated and the subsequent closed-form solutions of the same are obtained by using Fourier transformation technique. Two simultaneous analyses are performed for piles and raft and displacement compatibility is satisfied at the junction of the components. The proposed method is validated with dynamic centrifuge test results, available in the literature. In further parametric studies, the effect of loading frequency on the dynamic displacement response of CPRF is investigated. Also it is perceived that with an increase in raft flexibility by 60%, the horizontal load sharing proportion of raft reduces by 75%–65% for loose to dense sands, correspondingly. This study contributes significantly in understanding the steady-state response of CPRF under dynamic loading from an analytical perspective. Highlights: New analytical methodology to obtain dynamic response of flexible combined pile raft foundation (CPRF). Advanced two-parameter Pasternak medium is considered for representing soil. Closed-form solution for steady state response of CPRF under dynamic loading. Effect of the ratio of loading and natural frequency of CPRF on its dynamic displacement response. Effect of raft flexibility on horizontal load sharing proportions by components of CPRF.